Dye-sensitized solar cells using fluorone-based ionic liquids with improved cell efficiency - Pinto, Ana L. (2022)
POCI-01-0145-FEDER-016387. POCI-01-0145-FEDER-007265. UID/QUI/50006/2019. LISBOA-01-0145-FEDER-402-022125. SFRH/BD/135087/2017.